Translocator protein as an imaging marker of macrophage and stromal activation in RA pannus - Narayan, N; Owen, D; Mandhair, H; Smyth, E; Carlucci, F; Saleem, A; Gunn, R; Rabiner, E; Wells, L; Dakin, S; Sabokbar, A; Taylor, P (Society of Nuclear Medicine and Molecular Imaging, 2018)
Positron Emission Tomography (PET) radioligands targeted to Translocator protein (TSPO), offer a highly sensitive and specific means of imaging joint inflammation in rheumatoid arthritis (RA). Through high expression of TSPO on activated macrophages, TSPO PET has been widely reported in several studies of RA as a means of imaging synovial macrophages in vivo. However, this premise does not take into account the ubiquitous expression of TSPO. This study aimed to investigate TSPO expression in major cellular constituents of RA pannus; monocytes, macrophages, fibroblast-like synoviocytes (FLS) and CD4+ T lymphocytes, to more accurately interpret TSPO PET signal from RA synovium. Methods: 3 RA patients and 3 healthy volunteers underwent PET both knees using the TSPO radioligand 11C-PBR28. Through synovial tissue 3H-PBR28 autoradiography and immunostaining of 6 RA patients and 6 healthy volunteers, cellular expression of TSPO in synovial tissue was evaluated. TSPO mRNA expression and 3H-PBR28 radioligand binding was assessed using in vitro monocytes, macrophages, FLS and CD4+ T-lymphocytes. Results: 11C-PBR28 PET signal was significantly higher in RA compared to healthy joints (average SUV 0.82± 0.12 compared to 0.03± 0.004 respectively, p<0.01). Further, 3H-PBR28 specific binding in synovial tissue was approximately 10-fold higher in RA compared to healthy controls. Immunofluorescence revealed TSPO expression on macrophages, FLS and CD4+ T cells. In vitro study demonstrated highest TSPO mRNA expression and 3H-PBR28 specific binding, in activated FLS, non-activated and activated ‘M2’ reparative macrophages, with least TSPO expression in activated and non-activated CD4+ T lymphocytes. Conclusion: This study is the first evaluation of cellular TSPO expression in synovium, finding highest TSPO expression and PBR28 binding on activated synovial FLS and M2 phenotype macrophages. TSPO targeted PET may therefore have unique sensitivity to detect FLS and macrophage predominant inflammation in RA, with potential utility to assess treatment response in trials using novel FLS-targeted therapies.